Factors affecting proteoglycan synthesis and structure that modify the interaction with lipoproteins. (August 2009) - Yang, Sundy NY; Osman, Narin; Burch, Micah L; Little, Peter J
Atherosclerosis and its sequelae remain the major contributors to morbidity and premature mortality, despite the availability of the efficacious statin drugs. It has recently been demonstrated that human atherosclerosis in coronary arteries commences with the binding and retention of atherogenic ApoB-containing lipoproteins by modified proteoglycans. Vascular smooth muscle cells are the major source of proteoglycans in the vessel wall. A multitude of vasoactive factors stimulate the synthesis of proteoglycans and modify the structure of glycosaminoglycan chains produced by vascular smooth muscle cells and numerous diabetes and cardiovascular drugs prevent or reverse changes in proteoglycan synthesis. This review considers these factors and the extent to which they modify the interaction of proteoglycans with lipids and, thus, drive or delay the development of atherosclerosis.